2017
DOI: 10.3390/proteomes6010001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Analysis of Urine Reveals Down-Regulation of Acute Phase Response Signaling and LXR/RXR Activation Pathways in Prostate Cancer

Abstract: Detecting prostate cancer (PCa) using non-invasive diagnostic markers still remains a challenge. The aim of this study was the identification of urine proteins that are sufficiently sensitive and specific to detect PCa in the early stages. Comparative proteomics profiling of urine from patients with PCa, benign prostate hyperplasia, bladder cancer, and renal cancer, coupled with bioinformatics analysis, were performed. Statistically significant difference in abundance showed 20 and 85 proteins in the 2-D DIGE/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 61 publications
3
34
0
1
Order By: Relevance
“…Previous study suggested that loss of PPARγ may be an important step in the progression of UBC 13. Therefore, its down-regulation in PNO1 KD cells further indicated the role of PNO1 in the migration of UBC.The acute-phase response was the most significantly enriched down-regulated pathway involving the identified DEGs, which is characterized by alteration in the concentrations of a number of plasma proteins produced by the liver, in response to cytokines including IL-1, IL-6, IL-8, TNFα, etc during inflammatory response 16. 14 However, another study reported dramatically increased amplification of PPARγ in UBC tissues, especially those with lymph node metastasis and that PPARγ played an important role in 5673 cell migration and invasion 15.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Previous study suggested that loss of PPARγ may be an important step in the progression of UBC 13. Therefore, its down-regulation in PNO1 KD cells further indicated the role of PNO1 in the migration of UBC.The acute-phase response was the most significantly enriched down-regulated pathway involving the identified DEGs, which is characterized by alteration in the concentrations of a number of plasma proteins produced by the liver, in response to cytokines including IL-1, IL-6, IL-8, TNFα, etc during inflammatory response 16. 14 However, another study reported dramatically increased amplification of PPARγ in UBC tissues, especially those with lymph node metastasis and that PPARγ played an important role in 5673 cell migration and invasion 15.…”
mentioning
confidence: 85%
“…The PCP pathway participates in the regulation of the cytoskeleton. Therefore, its down-regulation in PNO1 KD cells further indicated the role of PNO1 in the migration of UBC.The acute-phase response was the most significantly enriched down-regulated pathway involving the identified DEGs, which is characterized by alteration in the concentrations of a number of plasma proteins produced by the liver, in response to cytokines including IL-1, IL-6, IL-8, TNFα, etc during inflammatory response 16.…”
mentioning
confidence: 89%
“…These receptors usually exist in biological and pathological pathways related to glucose, lipid homeostasis and the inflammatory response [83]. The proteomic study of urine in prostate cancer patients with a Gleason score of 6.9 ± 1.1 showed that LXR/RXR is activated and the signal of the acute-phase response is significantly downregulated [84]. Clathrin-mediated endocytosis is associated with the migration of prostate cancer cells [85].…”
Section: Rm-1 Prostate Cancer-bearing Micementioning
confidence: 99%
“…In the LXR/RXR activation pathway, LXR/RXR is involved in lipid metabolism, including inflammatory responses and cholesterol metabolism [115] . Studies of the comparative proteomic analysis of urine revealed a downregulation of acute-phase response signals and LXR/RXR activation pathways in prostate cancer [127] . Some of the identified pathways were involved in the body's immune response.…”
Section: Nutu-19 Cellsmentioning
confidence: 99%